Translation and Impact of the National Diabetes Prevention Program in Two Rural Settings: Participant Outcomes, Individual Experiences, and Recommendations - Jenifer J. Thomas; Bhibha M. Das; Lesley D. Lutes; Lacey Dickson; Parres Holliday; Brianna Adams; Hannah McNamee (Diabetology)
Background/Objectives: The National Diabetes Prevention Program (National DPP) assists individuals with lifestyle change for type 2 diabetes risk reduction through education, skills, and support. To further understand program effectiveness, implementation research needs to consider influences on retention, effectiveness, and sustainability of the program in rural settings. The purpose of this study was to understand National DPP implementation in two rural workplace settings as well as the factors that influence program participation and outcomes. Methods: Individuals who met criteria for being at risk for developing type 2 diabetes participated in two National DPPs. The first program (Technology-Augmented DPP) occurred in 2016 with the goal of understanding the role of psychosocial factors in relation to National DPP outcomes, and quantitative data were obtained from 47 participants. Variables of interest included the Lifestyle-Health-Related Self-Concept questionnaire (HRSC), weight, and physical activity. The second program (Hybrid-Format DPP) occurred in 2022 with the goal of understanding individual participant experiences within the program by conducting a reflexive thematic analysis on data obtained during a semi-structured group interview with 3 participants. Results: In the Technology-Augmented DPP, Lifestyle-HRSC dimensions of nutrition, social support, avoiding diabetes, and problem solving were associated with weight, steps per day, and activity minutes. In the Hybrid-Format DPP, the generated themes included Frequency Matters, Rules of Engagement, Promoting Self-Efficacy, and Bridging the Intention-Behavior Gap. Conclusions: Based on this study, a focus on understanding and responding to context-specific and participant-focused National DPP implementation is the essential next step in National DPP research. Prevention programs and policies individualized to people and communities will improve participation and outcomes. The National DPP should consider how to evolve to the changing needs of at-risk individuals in rural and underserved areas.